O silenciamento no texto jornalístico e a construção social da realidade - Hora, Carmem Daniela Spínola da (2008)
This research analyses the silencehood use by the A República journal (Natal/RN), today not being distributed, during the Second World War. Its objective is to unveil the production condition of the news texts, and it was observed that the use of silencehood as a speech strategy with its implications that falls upon the way of behaving and thinking of the society, all that time, influencing the reader in the construction of his image of the reality. During the coverage of the conflict by the local journal it was possible to also observe different speech marks that represented the change in attitude of the Brazilian Government, responsible for the control of what was spread as news. The country lived the dictatorship of the New State and as the war went on the government changed its speech, according to political, social and economical interest s thoughts being played, silencing themes in the name of the national security. We admit as research material journalistic texts that refer to the main facts that occurred during the six years of the world conflict and that is why we used as theoric-metodological support the Speech Analysis